2018
DOI: 10.1088/1612-202x/aac5ca
|View full text |Cite
|
Sign up to set email alerts
|

Spectrally shaped chirped pulse amplification of an all-normal dispersion Yb-doped fibre laser

Abstract: We show experimentally and theoretically that the spectral profile of the seed pulse of an Yb-doped fibre-based chirped pulse amplifier (CPA) plays a dominant role for achieving an ultrashort compressed pulse. The picosecond seed pulse from an all-normal dispersion Yb-doped fibre laser can be compressed to 350 fs with a peak power of 25 MW. Better compressed pulse quality and a shorter pulse was achieved by the spectrally shaped CPA system as opposed to the system without spectral shaping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…In 2016, R Y Sun et al reported a 1064 nm CPA system, which achieved a femtosecond pulse with a single pulse energy of 1.5 μJ and a pulse duration of 566 fs in a 30/250 μm YDF [12]. In 2018, Alexey Zaytsev et al presented a similar 1064 nm CPA system utilizing a 30/250 μm YDF, which delivered pulses with an single pulse energy of 8.8 μJ and a pulse duration of 350 fs [13]. In 2019, C Hong et al employed CPA technology in a 40/200 µm Yb-doped large-modearea photonic crystal fiber (LMA-PCF) at a wavelength of 1064 nm.…”
Section: Introductionmentioning
confidence: 99%
“…In 2016, R Y Sun et al reported a 1064 nm CPA system, which achieved a femtosecond pulse with a single pulse energy of 1.5 μJ and a pulse duration of 566 fs in a 30/250 μm YDF [12]. In 2018, Alexey Zaytsev et al presented a similar 1064 nm CPA system utilizing a 30/250 μm YDF, which delivered pulses with an single pulse energy of 8.8 μJ and a pulse duration of 350 fs [13]. In 2019, C Hong et al employed CPA technology in a 40/200 µm Yb-doped large-modearea photonic crystal fiber (LMA-PCF) at a wavelength of 1064 nm.…”
Section: Introductionmentioning
confidence: 99%